Pemanfaatan Bahan Lokal “Getah Nyatu” Untuk Memperkuat Ekonomi Kreatif Masyarakat Daerah Aliran Sungai (DAS) Kahayan di Kota Palangka Raya - Triyani, Triyani; Suprayitno; Kartika Ananda; Huda Musthofa; Angelika Putri (LPPM Universitas Palangka Raya, 2024)
The partner involved in this service activity is IKM Pandji. The problems faced by IKM Pandji partners are related to production and marketing problems. To solve this problem, the Community Entrepreneurship Assistant Lecturer Empowerment Program Team offers alternative solutions in the form of procuring more sophisticated production equipment, providing training and assistance in making nyatu sap crafts, marketing training and assistance through the IG, Tiktok, Facebook, Shopee, Lazada and Tokopedia platforms. Apart from that, this program also offers practical work and evaluation programs at each stage of the program. For problems in the production sector, the team applies methods of outreach activities, training and mentoring activities, as well as procurement of equipment to support the production of Getah Nyatu. Apart from that, in the marketing sector, the team applies training and mentoring methods which are intended to train and equip groups of craftsmen to have understanding and skills in marketing their handicraft products digitally. By promoting handicraft products digitally, it is hoped that Getah Nyatu crafts will attract the attention of consumers, both nationally and internationally. Marketing training through e-commerce platforms is expected to be able to provide understanding and skills in selecting media as a link for delivering advertising messages to consumers. This solution was provided to partners (IKM Pandji) with the aim of realizing the main objective, namely providing understanding and skills in producing crafts through optimizing local Getah Nyatu materials and being able to market their craft products at local, national and international market levels.